2017
DOI: 10.1002/ldr.2694
|View full text |Cite
|
Sign up to set email alerts
|

Aridity and Overgrazing Have Convergent Effects on Ecosystem Structure and Functioning in Patagonian Rangelands

Abstract: Over 65% of drylands are used for grazing of managed livestock. Understanding what drives grazing effects on the structure and functioning of rangelands is critical for achieving their sustainability. We studied a network of 239 sites across Patagonian rangelands (Argentina), which constitute one of the world's largest rangeland area. We aimed to (i) evaluate how aridity and grazing affect ecosystem structure and functioning and (ii) test the usefulness of the landscape function analysis (LFA) indices (stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 61 publications
(88 reference statements)
2
45
2
3
Order By: Relevance
“…It increases the persistence of vegetation patches under prolonged droughts. Similar negative effects of overgrazing in dry environments were also highlighted by Juan J. Gaitán et al (—this issue) in Patagonian rangelands, Argentina.…”
Section: Introductionsupporting
confidence: 78%
“…It increases the persistence of vegetation patches under prolonged droughts. Similar negative effects of overgrazing in dry environments were also highlighted by Juan J. Gaitán et al (—this issue) in Patagonian rangelands, Argentina.…”
Section: Introductionsupporting
confidence: 78%
“…Naturalness values decreased with increasing grazing intensity, which calls attention to the importance of setting and designing proper management intensities in rangelands. Even though in our case increasing grazing intensity did not lead to the severe degradation of grasslands, several studies identified overgrazing as a major cause of habitat degradation (Deák et al, ; Gaitán et al, ; Tóth et al, ).…”
Section: Discussioncontrasting
confidence: 57%
“…This is probably caused by the trampling effect of the larger-sized crossbred beef cattle, which is higher on wet soil compared to dry soil (Warren, Nevill, Blackburn, & Garza, 1986 (Deák, Valkó, Tóthmérész, et al, 2014c), also leading to decreased moisture indicator values. In the face of climate change, the interaction of grazing-and climate-induced drought will act as an important threat for the conservation values of rangelands (Gaitán et al, 2018;Webb et al, 2017). An option for mitigating the negative effects of climate change could be to apply grazing of traditional cattle breeds in the sensitive marsh areas.…”
Section: Conservation Valuementioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for declining pasture productivity are seemingly straightforward. Human-induced degradation has been attributed to over-grazing or other damaging land-use practices (Hilker et al 2014;Stevens et al 2016;Kairis et al 2015;Christianen et al 2014;Gaitán et al 2018). Often, the common property nature of pastures causes Garret Hardin's tragedy of commons (Hardin 1968), where multiple users compete for the resource.…”
Section: Introductionmentioning
confidence: 99%